Single-center retrospective study on Basidiobolomycosis: Characteristics, management, and outcomes - Huda Abbag; Alaa Al Juaid; Ahmad Alghamdi; Fatimah Alturkistani (Journal of Infection and Public Health, 2025)
Gastrointestinal basidiobolomycosis (GIB), a rare fungal infection caused by Basidiobolus ranarum, primarily affects children in tropical regions and often mimics other conditions, leading to delayed diagnosis. This study retrospectively analyzes nine pediatric cases of GIB diagnosed between 2013 and 2023 at a tertiary care center in Saudi Arabia. Patients had a median age of five years, with abdominal symptoms being the most common presentation (77.7 %). Laboratory findings included leukocytosis, eosinophilia, and elevated inflammatory markers. The ascending colon was the most frequently affected site (44.4 %). Histopathological examination confirmed fungal elements in all cases. All patients received voriconazole; 22.2 % were treated with both voriconazole and itraconazole. The mean treatment duration was 16 months. Complete resolution was achieved in 44.4 % of patients, while 22.2 % were lost to follow-up, and 22.2 % remained under treatment. GIB requires a high index of suspicion, particularly in patients with abdominal masses and eosinophilia. Diagnosis using minimally invasive methods and antifungal therapy, particularly voriconazole-based regimens, appear effective in managing this condition.